2011
DOI: 10.1242/jeb.049338
|View full text |Cite
|
Sign up to set email alerts
|

Polarised skylight and the landmark panorama provide night-active bull ants with compass information during route following

Abstract: SUMMARYNavigating animals are known to use a number of celestial and terrestrial compass cues that allow them to determine and control their direction of travel. Which of the cues dominate appears to depend on their salience. Here we show that night-active bull ants attend to both the pattern of polarised skylight and the landmark panorama in their familiar habitat. When the two directional cues are in conflict, ants choose a compromise direction. However, landmark guidance appears to be the primary mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 44 publications
7
106
0
Order By: Relevance
“…The findings extend the integration of multiple cues for navigation to another ant species tested in different conditions. Integration of multiple cues has now been shown in M. pyriformis (Reid et al, 2011), M. croslandi (Narendra et al, 2013), C. fortis (Collett, 2012) and M. bagoti (current results), across a range of cue manipulations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The findings extend the integration of multiple cues for navigation to another ant species tested in different conditions. Integration of multiple cues has now been shown in M. pyriformis (Reid et al, 2011), M. croslandi (Narendra et al, 2013), C. fortis (Collett, 2012) and M. bagoti (current results), across a range of cue manipulations.…”
Section: Discussionsupporting
confidence: 63%
“…Reid and colleagues (Reid et al, 2011) presented homing night-active bull ants (Myrmecia pyriformis) with a conflict between celestial and terrestrial cues. This was achieved by using a polarising filter that rotated the pattern of polarisation by 45 deg, thus creating a discrepancy between this cue and the unmanipulated terrestrial panorama.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that UV contrast is highly effective for sky segmentation and the resulting binary panoramic skyline images can support effective navigation in ants [29,30]. The night-active M. vindex may be forced to slow down their UV receptors not only to ensure sufficient skyline contrast for landmark guidance [28], but also to obtain reliable compass information from the dim pattern of polarized skylight in the evening twilight [24].…”
Section: Discussion (A) Three Spectrally Distinct Photoreceptors In Antsmentioning
confidence: 99%
“…Here we investigate head roll orientation in the nocturnal ant Myrmecia pyriformis Smith 1858, which has previously been shown to rely heavily on vision for navigation (Narendra et al, 2013c;Reid et al, 2011). We ask (1) whether nocturnal ants exhibit compensatory head movements to stabilise their gaze while walking, (2) to what extent their visual system is involved in head stabilisation, and (3) whether a change in ambient light intensity affects head stabilisation.…”
Section: Introductionmentioning
confidence: 99%